2000
DOI: 10.1021/bi001229u
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Indole by Cytochrome P450 Enzymes

Abstract: Indole is a product of tryptophan catabolism by gut bacteria and is absorbed into the body in substantial amounts. The compound is known to be oxidized to indoxyl and excreted in urine as indoxyl (3-hydroxyindole) sulfate. Further oxidation and dimerization of indoxyl leads to the formation of indigoid pigments. We report the definitive identification of the pigments indigo and indirubin as products of human cytochrome P450 (P450)-catalyzed metabolism of indole by visible, (1)H NMR, and mass spectrometry. P450… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
217
0
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 273 publications
(233 citation statements)
references
References 38 publications
(61 reference statements)
7
217
0
3
Order By: Relevance
“…Hydroxylation of Indole by HbpA ind -Indole is oxidized by different oxygenases that contain either protein-bound iron or cytochrome to activate molecular oxygen (6,32). No flavoprotein oxygenase has thus far been shown to accept indole as a substrate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hydroxylation of Indole by HbpA ind -Indole is oxidized by different oxygenases that contain either protein-bound iron or cytochrome to activate molecular oxygen (6,32). No flavoprotein oxygenase has thus far been shown to accept indole as a substrate.…”
Section: Discussionmentioning
confidence: 99%
“…Naphthalene dioxygenase was soon found not to be the only enzyme capable of indole oxidation: several other oxygenases that accept indole as a substrate have been identified (5)(6)(7)(8)(9)(10). These are either enzymes similar to naphthalene dioxygenase that activate oxygen with iron centers or members of the cytochrome P450 family (6,11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that indole acts as an inhibitor of CYP264A1 from S. cellulosum So ce56 and CYP109B1 from Bacillus subtilis (Girhard et al, 2010). In addition, some P450 enzymes are known to convert indole, and in this way competing with the normal substrate (Gillam et al, 2000). In case of the two members of the CYP267 family, the presence of 600 mM indole decreases the product formation in vitro by up to 40% for CYP267B1 and by up to 85% in the case of CYP267A1 (Supplemental Fig.…”
Section: Optimization Of the E Coli-based Whole-cell Bioconversion Smentioning
confidence: 97%
“…After extensive consideration of the cause of this apparent artifact, we determined the cause of the phenomenon in collaboration with the laboratory of Prof. F. H. Arnold at the California Institute of Technology. The blue color was indigo, probably the oldest dye known to man (13,14).…”
Section: Indigo Formation In Bicistronic E: Coli Expression Systemsmentioning
confidence: 99%